Identification of osteogenic differentiation-related miRNA-mRNA regulatory network of human periodontal ligament stem cells: Osteogenic differentiation-related miRNA-mRNA regulatory network - Chen, Zhenrong; Long, Lulu; Wan, Mianjia; Huang, Min; Wu, Haijuan; Huang, Qun (Cellular and Molecular Biology, 2024)
This study aimed to investigate the hub genes and miRNA–mRNA regulatory network around periodontal ligament stem cells (PDLSC) for osteogenic differentiation through bioinformatic analysis. The dataset with osteogenic differentiation of human PDLSC was downloaded from the GEO database. The Weighted gene coexpression network analysis (WGCNA) was performed to identify key modules and hub genes. In addition, differentially expressed genes (DEGs) analysis was conducted with limma. The functional enrichment of differentially expressed hub genes was implemented with KEGG and GSEA analysis. The targeted genes of differentially expressed miRNA were predicted based on miRWalk database. The miRNA-mRNA interaction network of osteogenic differentiation of PDLSC was constructed and visualized. The WGNCA results showed that the light-cyan module was positively correlated with osteogenic differentiation (r=0.98, P<0.05). A total of 3125 hub genes and 1426 differentially expressed hub genes were detected in OG group. Innate immune-related signaling pathways and metabolic pathways were involved in the osteogenic differentiation. In addition, total of 2 upregulated miRNAs with 63 targeted DEGs and 6 downregulated miRNAs with 214 targeted DEGs were detected, which contributed to osteogenic differentiation by regulating amino acid metabolism signaling pathway. We identified hub genes and miRNA–mRNA regulatory network contributing to osteogenic differentiation of human PDLSC, which will provide novel strategy for periodontal disease therapy.